After Dirigisme: Globalization, Democratization, the Still Faulted State and its Social Discontent in Korea - Park, Hun Joo (Pacific Review, 2002)
The post-1997 Korean state in crisis and reform provides an excellent testing ground for the claim that the homogenizing forces of globalization and the international financial market are proving victorious over statist models of political economy. By examining the limits and capacities of the top-down, authoritarian state in its current form and its continuing social consequences, this paper provides an analytic account of the dysfunction of Korean developmental statism. This diseased dirigisme problematique, however, contrasts with an ‘opening-markets-solves-most-problems’ approach; an opening of markets, no matter how generally desirable, will not in itself solve problems of distorted development. Reconstruction of strong Korean statism is indispensable to Korea's long-term socio-economic health.